Service-Level Agreements in Call Centers: Perils and Prescriptions - Milner, Joseph M.; Olsen, Tava Lennon (Management Science, 2008)
Acall center with both contract and noncontract customers was giving priority to the contract customers only in off-peak hours, precisely when having priority was least important. In this paper, we investigate whether this is rational behavior on the part of the call center and what the implications are for customers. In particular, we show that under contracts on the percentile of delay, which are commonly used in the call center industry, this is rational behavior, at least under the approximating asymptotic regime considered in this paper. We then suggest other contracts that do not result in this type of undesirable behavior from a contract customer's perspective. We compare the performance of the different contracts in terms of mean, variance, and outer percentiles of delay for both customer types using both numerical and asymptotic heavy-traffic analyses. We argue that including terms reflecting the second moment of delay in a contract would be beneficial to contract customers and, in a sense, fairer.